Methodological Approaches to Validation of Therapeutic Recombinant Proteins Production Based on the Quality by Design Concept - N. V. Stratonova; A. S. Lisov; A. N. Morozov; D. V. Tyupa; R. A. Khamitov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Validation of production processes based on the Quality by Design (QbD) principles calls for thorough scientific understanding of the processes and enhancement of their stability by implementation of new technologies. The aim of the study consisted in substantiating a QbD-based technological approach to validation of commercial production of dornase alfa. For this purpose a design space was established in a scale-down model, i.e. 2 L reactors; the model was shown to be representative in terms of all parameters except for the reactor size; the similarity of hydrodynamic conditions, design characteristics and operation modes of laboratory, pilot and commercial scale reactors was established; the process scalability was demonstrated by using the PCA (Principal Component Analysis) multivariate mathematical model including the volume range of 2–1000 L, input and output process parameters and product quality attributes for a number of recombinant therapeutic products derived from the same CHO cell line and expression construction as dornase alfa producer. The article demonstrates the applicability of engineering space, which includes bioreactor design features and production process parameters, to different production scales by implementing 3 processes at the pilot scale (100 L) and 2 processes at the commercial scale (1000 L) and building a PCA model based on the obtained data.